Robot‐assisted minimally invasive esophagectomy for esophageal cancer: Meticulous surgery minimizing postoperative complications. Issue 6 (16th August 2020) - Hosoda, Kei; Niihara, Masahiro; Harada, Hiroki; Yamashita, Keishi; Hiki, Naoki
Abstract: Minimally invasive esophagectomy (MIE) has been reported to reduce postoperative complications especially pulmonary complications and have equivalent long‐term survival outcomes as compared to open esophagectomy. Robot‐assisted minimally invasive esophagectomy (RAMIE) using da Vinci surgical system (Intuitive Surgical, Sunnyvale, USA) is rapidly gaining attention because it helps surgeons to perform meticulous surgical procedures. McKeown RAMIE has been preferably performed in East Asia where squamous cell carcinoma which lies in more proximal esophagus than adenocarcinoma is a predominant histological type of esophageal cancer. On the other hand, Ivor Lewis RAMIE has been preferably performed in the Western countries where adenocarcinoma including Barrett esophageal cancer is the most frequent histology. Average rates of postoperative complications have been reported to be lower in Ivor Lewis RAMIE than those in McKeown RAMIE. Ivor Lewis RAMIE may get more attention for thoracic esophageal cancer. The studies comparing RAMIE and MIE where recurrent nerve lymphadenectomy was thoroughly performed reported that the rate of recurrent nerve injury is lower in RAMIE than in MIE. Recurrent nerve injury leads to serious complications such as aspiration pneumonia. It seems highly probable that RAMIE is beneficial in performing recurrent nerve lymphadenectomy. Surgery for esophageal cancer will probably be more centralized in hospitals with surgical robots, which enable accurate lymph node dissection with less complications, leading to improved outcomes for patients with esophageal cancer. RAMIE might occupy an important position in surgery for esophageal cancer. Abstract : Robot‐assisted minimally invasive esophagectomy (RAMIE) is rapidly gaining attention. RAMIE has been reported to lead to lower rates of recurrent nerve injury than conventional minimally invasive esophagectomy, when recurrent nerve lymphadenectomy was thoroughly performed. RAMIE might occupy an important position in surgery for esophageal cancer.